Food safety practices of home-based baking business in Quezon City - Jota, Angelica Marie L.
This study examines the food safety practices of home-based baking businesses in Quezon City, focusing on their food safety knowledge and practices from procurement to delivery. The study involved 60 home bakers, with a subsample of 10 interviewed for deeper insights. Most bakers operated on an upon order basis and had limited formal food safety training, relying on self-learning or generational knowledge. They demonstrated awareness of food safety principles, emphasizing safe preparation, quality maintenance, and contamination prevention. Although many home bakers were unfamiliar with the FATTOM concept, they understood the importance of temperature control and the impact of oxygen on food safety. In the four stages of production, they mostly adhered to good practices, such as checking ingredient quality, storing items at correct temperatures, and maintaining hygiene, but needs improvement in packaging, labelling, and use of protective clothing. Delivery practices were generally safe, though some bakers lacked proper packaging for delicate items. Complaints were mostly about physical contamination or structural damage rather than foodborne illnesses. Most bakers effectively managed ingredient spoilage by using the FIFO method and managing well their inventories. Lastly, many bakers took precautions to prevent direct contamination from rodents and pests except for one baker where fecal matter of pests and rodents find their way to plates used for baking. Despite some challenges, the study indicates that home bakers were generally committed to food safety, with a few areas for improvement. The results of the study emphasized the need for substantial food safety topics in the basic education and the need for home bakers and entrepreneurs whose main products are food to have the necessary training in essential concepts in food safety.